Utilization Of Onion Waste Applied To Green Mustard Plants As Liquid Organic Fertilizer (POC) In Kampung Baru Village, Bilah Barat District - Rahmaniah; Yana Linda br Jabat, Yelfi; Sibuea, Nunti (Universitas Mataram, 2024)
This socialization and training discusses making liquid organic fertilizer from shallot waste.Shallots are one of the leading horticultural commodities which are included in the spice vegetables which are usually used as cooking spices. Apart from being used as a cooking spice, shallots can also be used as organic fertilizer, because shallots can help plant growth and can stimulate the growth of plant shoots. Organic fertilizer is fertilizer that comes from dead plants, which have gone through a fermentation process, in solid or liquid form. The objectives of this activity are 1) To provide outreach and training about making liquid organic fertilizer. 2) to increase public awareness that shallot waste can be used as organic fertilizer. The method of this activity is to approach the community and farmer groups in Kampung Baru Village by providing knowledge to the community about making liquid organic fertilizer and practicing it directly. This activity involved farmer groups and PKK women in Kampung Baru Village. From the results of the activities that have been carried out, it can be concluded that the socialization and training are very useful because they have provided knowledge and knowledge about making liquid organic fertilizer from shallot waste.